World Food Security A History since 1945 - Shaw, D. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
This book is the first comprehensive account of the numerous attempts made since the Second World War to provide food security for all. It provides a reference source for all those involved and interested in food security issues.